Discovery of novel tepovirus genomes with a nucleic acid-binding protein homolog by systematic analysis of plant transcriptome data - Dongjin Choi; Hyerin Park; Seungwoo Baek; Myeung Seok Choi; Sylvain Legay; Gea Guerriero; Jean-François Hausman; Yoonsoo Hahn (Acta Virologica)
Some plant RNA viruses in the family Betaflexiviridae encode a nucleic acid-binding protein (NABP) that facilitates infection by suppressing the host RNA silencing response. Previously, no members of the genus Tepovirus within this family were known to possess a NABP homolog. In this study, we identified the genome sequences of 21 novel Betaflexiviridae viruses: 17 represent new members of Tepovirus, and four may be founding members of a new genus closely related to the genus Vitivirus. Notably, five of these newly identified tepoviruses contain a NABP-like open reading frame (ORF). Sequence comparison and phylogenetic analysis of NABP homologs suggest these tepoviruses independently acquired a NABP-like ORF from diverse sources. The identification of 17 novel viruses substantially enhances our understanding of the genetic diversity within the genus Tepovirus. This study further highlights the role of recombination in the genome evolution and diversity of Betaflexiviridae.